Piety, transgression, and the feminist debate on Muslim women: Resituating the victim-subject of honor-related violence from a transnational lens - Jamal, Amina (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
While I strongly endorse anti-imperialist feminist attempts to uphold devout Muslim women’s gendered agency, I am concerned that these arguments fail to disrupt the intransigent association of freedom, particularly individual freedom, with secularism, and communitarian restraint with Islam. It is not surprising, therefore, that victim-subjects of honor-related violence, whether in a secular state such as Canada or an Islamic state like Pakistan, are discursively installed within the universal secular sphere and reevicted from the religious and cultural community. I propose the notion of transgressive piety rather than the dichotomy of secular society versus pious community within which to problematize gendered Muslim subjects. The transgression of ritualistic and institutionalized practices is associated with practices termed Sufism. Muslim feminists may use the idea of transgressive piety to offer faith-based support to those gendered subjects whose transgressive acts, appearance, or practices define them as legitimate targets of family, community, or state-based violence. In so doing, we may also challenge doctrinaire and narrow definitions of the Muslim Ummah, the all-encompassing and transcendent community of Muslims.